2017
DOI: 10.1007/s00425-017-2721-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cucumber (Cucumis sativus L.) fruit size and shape results from multiple components acting pre-anthesis and post-pollination

Abstract: Morphological, QTL, and gene expression analyses indicate variation in cucumber fruit size and shape results from orientation, timing, and extent of cell division and expansion, and suggest candidate gene factors. Variation in cucumber (Cucumis sativus L.) fruit size and shape is highly quantitative, implicating interplay of multiple components. Recent studies have identified numerous fruit size and shape quantitative trait loci (QTL); however, underlying factors remain to be determined. We examined ovary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 68 publications
5
37
0
Order By: Relevance
“…Frequency of cell division is critical to fruit morphogenesis in a variety species such as Tomato [30][31][32][33], melon [37], pumpkin [35], cucumber [36][37][38][39]. In present study, we found that the fruit tip shape in 186 cucumbers inbred lines also were a complex trait and exhibit significant variations with angle range from 99 to 173° and fruit tip index range from 1.4 to 3.5.…”
Section: Orientation Of Cell Division Is Critical To Fruit Tip Develosupporting
confidence: 47%
“…Frequency of cell division is critical to fruit morphogenesis in a variety species such as Tomato [30][31][32][33], melon [37], pumpkin [35], cucumber [36][37][38][39]. In present study, we found that the fruit tip shape in 186 cucumbers inbred lines also were a complex trait and exhibit significant variations with angle range from 99 to 173° and fruit tip index range from 1.4 to 3.5.…”
Section: Orientation Of Cell Division Is Critical To Fruit Tip Develosupporting
confidence: 47%
“…6a ; Supplementary Table 7 ). In cucumber ( Cucumis sativus ), a species closely related to melon, the fruit shape QTL fs3.2 interval contains CsOFP15 , a gene that is lower expressed in cucumber varieties with an elongated fruit 19 . This is expected if CsOFP15 controls cucumber fruit shape.…”
Section: Resultsmentioning
confidence: 99%
“…Cucumbers (Cucumis sativus L.), harvested immaturely and consumed fresh or processed as pickles, is an important vegetable crop cultivated worldwide [1]. Fruit size and shape of cucumbers are usually determined by fruit length (FL), diameter (FD), or the length-by-diameter ratio (Fruit shape index, FSI) [2,3]. Fruit size is a crucial domestication trait in cucumber [4], and it displays tremendous variation, from 5 to 60 cm in length [5,6].…”
Section: Introductionmentioning
confidence: 99%